2017
DOI: 10.5812/zjrms.10074
|View full text |Cite
|
Sign up to set email alerts
|

Androgenetic Alopecia: A Chronic or Pubertal Onset Disease Retarded by Blood Donation

Abstract: Background: Androgenetic alopecia is the main cause of hair loss and common baldness that affects psychological more than physiological aspects of people's lives. Studies have shown that this multi factorial disorder is initiated by androgens secretion in pubertal period, minerals limitations, autoimmunity, mental stress, genetic predisposition and some alterations in hematological factors. Objectives: The aim of this study was to evaluate the involvement of hematologic parameters in this disease using a case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…In our study, PLT count was found to lower in AGA patients compared to controls without significant difference. Current results were consistent with that of [11] This study showed that, AGA group showed significantly higher MPV when compared to control group [p<0.001 for each].This disagrees with İslamoğlu and Demirbaş, [12] who found that the MPV values did not show any significant difference between the two groups.…”
Section: Benhasupporting
confidence: 79%
“…In our study, PLT count was found to lower in AGA patients compared to controls without significant difference. Current results were consistent with that of [11] This study showed that, AGA group showed significantly higher MPV when compared to control group [p<0.001 for each].This disagrees with İslamoğlu and Demirbaş, [12] who found that the MPV values did not show any significant difference between the two groups.…”
Section: Benhasupporting
confidence: 79%